Slovenes in Neighbouring Countries as Part of the Curriculum in Primary and Secondary Schools in Slovenia - Čok, Lucija (Revija za elementarno izobraževanje, 2021)
Slovenes live as an autochthonous minority in neighbouring countries of Italy,Austria, Hungary and Croatia. The common European space allows them todevelop a cultural area with far-reaching implications. An analytical review ofSlovenian minorities through the content of curricula of primary andsecondary schools examined the presence of topics related to them.Researchers that analysed the school curricula and textbooks with a specialquestionnaire for pupils, students and general population assessed the currentsituation in school practice. Following the processing of quantitative data andconsultation meetings with experts changes and additions to the curricula ofprimary and secondary schools were proposed.